The effect of self-etching adhesive system associated with different energy densities of Nd:YAG laser on microtensile bond strength to dentin - Barcellos, Daphne Camara [UNESP]; Holleben, Priscila [UNESP]; Fonseca, Beatriz Maria [UNESP]; Sabino, Bruna de Cássia [UNESP]; Gonçalves, Sérgio Eduardo de Paiva [UNESP] (Springer Nature, 2018)
Purpose: This study has evaluated the dentin bond strength of Clearfil SE Bond (CSEB) Self-Etching Adhesive System associated with different energy densities of Nd:YAG laser through unpolymerized adhesive. Methods: The dentin surfaces of 90 bovine teeth were flattened and divided into six groups (n = 15): G1 (control), CSEB + photopolymerization; G2, CSEB + Nd: YAG laser (74.64 J/cm2) + photopolymerization; G3, CSEB + Nd: YAG laser (100 J/cm2) + photopolymerization; G4, CSEB + Nd: YAG Laser (125 J/cm2) + photopolymerization; G5, CSEB + Nd: YAG Laser (149.28 J/cm2) + photopolymerization; and G6, CSEB + Nd: YAG Laser (174.16 J/cm2) + photopolymerization. Resin restorations were made after sectioning the teeth and submitted to microtensile bond strength test. Results: Data were submitted to ANOVA and Tukey’s test (5%), resulting in a value of 0.0002. G2 (74.64 J/cm2) presented higher bond strength values compared to G1 (control), G5 (149.28 J/cm2), and G6 (174.16 J/cm2). Also, G3 (100 J/cm2) presented higher bond strength values compared to G5 (149.28 J/cm2) and G6 (174.16 J/cm2). Conclusion: Nd:YAG laser irradiation (74.64 J/cm2) through unpolymerized CSEB can improve dentin bond strength of CSEB compared to non-irradiated dentin and also increase dentin bond strength compared to higher Nd:YAG laser irradiations (149.28 J/cm2 and 174.16 J/cm2).
Keywords: Dentin bond strength; Nd:YAG laser; Self-etch adhesive